2000
DOI: 10.1063/1.373747
|View full text |Cite
|
Sign up to set email alerts
|

Defect dominated charge transport in amorphous Ta2O5 thin films

Abstract: Ta 2 O 5 is a candidate for use in metal-oxide-metal ͑MOM͒ capacitors in several areas of silicon device technology. Understanding and controlling leakage current is critical for successful implementation of this material. We have studied thermal and photoconductive charge transport processes in Ta 2 O 5 MOM capacitors fabricated by anodization, reactive sputtering, and chemical vapor deposition. We find that the results from each of these three methods are similar if one compares films that have the same thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(74 citation statements)
references
References 36 publications
9
64
1
Order By: Relevance
“…It has three oxygen sites: one interlayer and two intralayer. The GGA band gap is 1.8 eV and is improved by sX-LDA functional to 4.0 eV, in agreement with the experimental value [45]. Crystalline TaO2 has a rutile structure and is shown to be metallic by both GGA and sX-LDA functionals, which is consistent with a recent calculation [19] and the XPS observations [19].…”
Section: Resultssupporting
confidence: 80%
“…It has three oxygen sites: one interlayer and two intralayer. The GGA band gap is 1.8 eV and is improved by sX-LDA functional to 4.0 eV, in agreement with the experimental value [45]. Crystalline TaO2 has a rutile structure and is shown to be metallic by both GGA and sX-LDA functionals, which is consistent with a recent calculation [19] and the XPS observations [19].…”
Section: Resultssupporting
confidence: 80%
“…Table 2 shows the calculated donor density of tantalum in KOH solutions. The density of donors (N D ) is in the order of magnitude of 10 20 to 10 22 cm −3 , which is analogous to those reported previously [43]. These high values of the donor densities can be thought as a higher density of oxygen vacancies in the passive film [12,43].…”
Section: Accepted Manuscriptsupporting
confidence: 53%
“…As long as the thin native oxide on Ta is concerned, however, a depth-profiling study of tantalum metal/oxide interface by combining X-ray photoelectron spectroscopy (XPS) with Ar + ion bombardment has revealed that Ta sub-oxides exist particularly near metal/oxide interface, which have a distribution that is different from the thermally grown oxide films [42]. On the other hand, voltammetry and photoconductivity measurements have shown that point defects are predominantly located near metal/passive film interfaces and their density is vastly reduced moving toward bulk Ta 2 O 5 [43]. Table 2 shows the calculated donor density of tantalum in KOH solutions.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Substantial difference in the equivalent oxide thickness is observed. The lowest value of 2.27 nm is obtained for Al gate and is attributed to the known reactivity of Al with Ta 2 O 5 [26].…”
Section: Frequency Dependence Of -Characteristicsmentioning
confidence: 97%